2016
DOI: 10.3390/nu8120776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Pregnancy BMI on B Vitamin and Inflammatory Status in Early Pregnancy: An Observational Cohort Study

Abstract: Maternal nutrition and inflammation have been suggested as mediators in the development of various adverse pregnancy outcomes associated with maternal obesity. We have investigated the relation between pre-pregnancy BMI, B vitamin status, and inflammatory markers in a group of healthy pregnant women. Cobalamin, folate, pyridoxal 5′-phosphate, and riboflavin; and the metabolic markers homocysteine, methylmalonic acid, and 3-hydroxykynurenine/xanthurenic acid ratio (HK/XA); and markers of cellular inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…The regression analysis in cohort 1, after correcting for multiple confounders, we found that B12 is independently associated with BMI whereas in cohort 2, in addition to B12, social deprivation was also associated with BMI. The association between BMI and B12 has been shown in other studies in pregnant women 15,16,17 but also in adolescents 14 and in women of childbearing age 28 . In addition, B12 deficiency may be causally related to dysglycaemia 9 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The regression analysis in cohort 1, after correcting for multiple confounders, we found that B12 is independently associated with BMI whereas in cohort 2, in addition to B12, social deprivation was also associated with BMI. The association between BMI and B12 has been shown in other studies in pregnant women 15,16,17 but also in adolescents 14 and in women of childbearing age 28 . In addition, B12 deficiency may be causally related to dysglycaemia 9 .…”
Section: Discussionsupporting
confidence: 53%
“…In children and adolescents, increase in BMI 13 and IR 14 have been associated with low B12 levels. Furthermore, studies in early pregnancy have focussed on association between lower maternal micronutrient status (B12, folate, iron) with pre-pregnancy overweight and obesity in mothers 15,16,17 , with lower micronutrients in low-birth weight infants 18 and with higher BMI and heart rate in children at age 5-6 19 . Our in vitro studies have shown that B12 deficiency in adipocytes altered DNA methylation levels 2 of the transcription factors of lipid regulation 2 and the adipose derived miRNAs targeting IR 3 thereby suggesting that B12 deficiency dysregulates epigenetic mechanisms.…”
Section: Sdmentioning
confidence: 99%
“…Folate connections to the association are also supported by maternal obesity effects. Since serum folate levels are inversely related to pre-pregnancy body mass [131], association findings would be expected, and do occur. Despite late macrosomia with obesity-related metabolic disturbances, there is excess growth restriction early on [132], as well as increases in limb reductions; anorectal, renal, and cardiovascular anomalies [133][134][135]; fertility issues [136]; prematurity; early losses and stillbirth; and possibly perinatal difficulties [137].…”
Section: Folate and Methylationmentioning
confidence: 93%
“…A complete distribution of maternal BMI is needed to fully characterize these possible fetal outcomes. Many prior studies have not been able to disentangle the influence of maternal BMI from cooccurring health-related (eg, diabetes, hypertension) factors, 16 which is important to help inform preventive efforts.…”
Section: Introductionmentioning
confidence: 99%